Fatty acid uptake by Caco-2 human intestinal cells - P J Trotter; S Y Ho; J Storch (Journal of Lipid Research, 1996)
The Caco-2 human enterocytic cell line was used to study the kinetics and mechanism of intestinal long chain fatty acid uptake. Initial rates of palmitate (16:0), oleate (18:1), and octanoate (8:0) uptake were determined for adherent cells at greater than 7 days confluence. Uptake of long chain 18:1 and 16:0 by cells grown on coverslips was saturable with an apparent Km of 0.3 microM, but also included a notable diffusive component. Uptake of short chain 8:0, on the other hand, was linear up to 10 microM. Cells grown on permeable Transwell filters were used to study uptake at the apical versus the basolateral membrane. Uptake of long chain (18:1 and 16:0), but not short chain (8:0), fatty acid was saturable at both surfaces with a similar Km of 0.3 microM. In addition, long chain but not short chain fatty acid uptake was competitively inhibitable. Western blot analysis demonstrated that Caco-2 cells express a protein immunoreactive with antibodies to the rat liver plasma membrane fatty acid binding protein (FABPpm), which is thought to be involved in long chain fatty acid transport. Nevertheless, long chain fatty acid uptake was not inhibited by pretreatment of the cells with an FABPpm antibody, nor by pretreatment with two proteases. These data support a saturable component in the transport of long chain but not short chain fatty acids by human intestinal epithelial cells, which may involve an as yet unknown plasma membrane protein.